Knee denervation as a chronic knee pain prevention method after knee arthroplasty - Bilykh, Ye. O. (Запорізький державний медичний університет, 2021)
The aim of the study. To determine the effectiveness of the pain syndrome prevention in the postoperative period after knee arthroplasty with RFNA method. Materials and methods. In this study, we included 44 patients with knee ostheoarthrits of the III-IV stage. In study group patients had arthroplasty of one knee and underwent preoperative modified procedure of the continuous RFNA of the genicular and cutaneous nerves of the incision area under ultrasound guidance.
Keywords: тези